A contribuição das práticas de gestão de tecnologia para o desenvolvimento de capacidades tecnológicas na empresa IOTA bioenergia - Silva, Adriane Carla Anastácio da (2010)
The aim of this study was to evaluate the contribution of TMP in the development of technological capabilities in the IOTA Bioenergy company. For the development of the study, the proposed problem was: What is the contribution of technology management practices for the development of technological capabilities in the IOTA Bioenergy company? The inductive method used allows the applied research approach; qualitative and quantitative; exploratory and a case study. The data was collected using semi-structured interviews and questionnaires among those in charge of the following areas: IT, Industrial Automation, R&D, HR, Environmental, Ethanol Production and Cogeneration Energy generating inferences, these analyzed through content analysis and the questionnaires through quantitative analysis. The theoretical connects the themes: the renewable energy scenario, the concept of technology connected to the innovation, highlighting the technological capability, to the technology management and its practices. It is estimated that the researched company needs, by knowing the market and aiming its technological and market strategies at fixing the leadership position in the sector, enhanced the formal practice of 15, and informal, 3 TMP, that allowed the mapping of the actions which characterize technological capabilities, according to Silva (2003), based on the TMP. Thus, TMP contribute to analyze the market, monitor technological development aimed at the specification of new products and processes; provide through benchmarking the best practices of the best in the sector; incorporate and examine trends in technological forecasting techniques; analyze opportunities and risks of the technological advances; evaluate potential projects; program technological changes; avoid duplication of investments in R&D from actions such as patents analysis; share existing resources, internally and externally with companies (competitors or not), group associations, technological research centers and/or universities and encouraging cooperation, in a multidisciplinary work, promoting the networking and management teams; apply the existing resources in its portfolio, in a continuous improvement process; conduct environmental assessment by applying the principles of sustainable development; fulfill the policies of environmental responsibility; reduce waste and costs in a lean manufacturing process that prevents or mitigates environmental impacts of bioenergy production.